PREDICTING FINANCIAL DISTRESS OF GARMENT AND TEXTILE COMPANIES LISTED IN INDONESIAN STOCK EXCHANGE (IDX) FOR THE YEAR OF 2012-2016 - Billy, Billy B1024131009 (Jurnal Manajemen Update, 2018)
ABSTRACTUnderstanding financial distressed has the meaning of difficulty of funds either in the sense of funds in terms of cash or in terms of working capital. As asset liability management is instrumental in the arrangement to keep the financial distressed. Bankruptcy will happen quickly to companies that are in a country that is experiencing economic difficulties, because of economic difficulties will trigger the rapid bankruptcy of companies that may have been sick then getting sick and bankrupt. Based on this, bankruptcy is an unhealthy company condition in continuing its business due to inability to compete resulting in a decrease in profitability. Prediction of bankruptcy can be said as a forecast of the level of bankruptcy that will occur in a company. Prediction bankruptcy itself can be known by using analysis. Bankruptcy is the inability of the company to pay the debt when a company can’t pay their debt, it will lose its power to finance their business activities and gain the revenue. In this research, the Textile and Garment companies becomes the subject to test if they are in financial distress situation or not in the period of 2012-2016.To find the financial distress, the variables used in this study are working capital to total assets ratio (X1), retained earnings to total assets ratio (X2), earnings before interest and tax to total assets ratio (X3), market value of equity to total liabilities ratio (X4), sales to total assets ratio (X5). Finally, after we get the result of financial distress, the Logistic Regression is used to determine if some variable like Age (X6), ROA (X7), Liquidity (X8), and Sales (X9) has significant impact or not to the financial distress. The result show that the textile and garment industry is in financial distress with ROA and Sales as a significant variable that impacted it.Keywords: Financial Distress, Working Capital, Retained Earnings, Earning Before Tax, Logistic Regression, Sales.